Dual FAAH and MAGL inhibition might play a key role in visceral pain - Sakin, Yusuf Serdar; Tanoğlu, Alpaslan; Gülşen, Mustafa (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Sakin YS, Tanoğlu A, Gülşen M. Dual FAAH and MAGL inhibition might play a key role in visceral pain.Turk J Gastroenterol 2018; 29: 625-6.